Restless arms syndrome with oral olanzapine: case based review. Issue 12 (December 2022) - Kuang, Qijie; Zhou, Sumiao; Huang, Rumeng; Zheng, Yingjun; She, Shenglin
Abstract: Background: Restless arms syndrome (RAS) is a specific variant of restless legs syndrome (RLS). RAS is characterised by an uncomfortable, painful, burning or uneasy sensation confined to the arm. Case presentation: We report a case of RAS with oral olanzapine, which improved with medication reduction. In addition, all reported cases of RAS were reviewed to explore the underlying mechanisms, diagnosis and treatment for psychiatric drug-induced RAS. The literature review and new case suggest that iron deficiency may be a predisposing factor for RAS. Psychiatric medications are closely associated with RAS, especially olanzapine, quetiapine, and mirtazapine. Discontinuation is the recommended treatment for psychotropic drug-induced RAS, while α2δ calcium channel ligand drugs and benzodiazepines may be considered. Conclusion: In conclusion, psychiatrists should be alert to the possibility of RAS when administering psychiatric medications for the first time to psychiatric patients with iron deficiency. Abstract : Restless arms syndrome (RAS); Case report; Olanzapine.